El impacto del boom latinoamericano en los escritores serbios - Kovačević Petrović, Bojana (Acta Hispanica, 2016)
In this work we want to show thestrong links between Spanish-American andSerbian writers, through the books translatedfrom Spanish and works written in Serbian.Assuming that each writer is above all a goodreader, and considering the importance of translationfor literature in general, we have investigatedthe influence of Borges, Cortázar, Fuentes,García Márquez and Vargas Llosa on Serbianwriters since the 1950s until today. Throughauthentic testimonies - interviews made for thisresearch - and the reviews and analysis of booksand particular texts influenced by the authors ofthe boom, we will present a creative variety andauthentic literary creation of a small country withmany translations and dedicated writers, andshow that the great impact of Spanish-Americanliterature in Serbia began half a century ago andnever ceased.